Intellectuals - Johnson, Paul, 1928- (Harper & Row, 1990)
This volume presents a portrait of the minds that have shaped the modern world. In a series of case studies, Rousseau, Shelley, Marx, Ibsen, Tolstoy, Hemingway, Bertrand Russell, Brecht, Sarte, Edmund Wilson, Victor Gollancz, Lillan Hellman, Cyril Connolly, Norman Mailer, James Baldwin, Kenneth Tyan, Noam Chomsky, and others are revealed as intellectuals both brilliant and contradictory, magnetic and dangerous. The author examines the rise of the intellectual as a sort of secular seer and moral arbiter, a role once filled by the priest or soothsayer. These intellectuals, in the author's opinion, promote themselves as possessing the moral authority to transform society, a claim that the author disputes.